Effect of slaughter handling conditions and animal temperament on bovine meat quality markers = Efecto del manejo y del temperamento animal sobre indicadores de calidad de la carne bovina - Pighin, Darío Gabriel; Davies, Patricio; Grigioni, Gabriela Maria; Pazos, Adriana Alejandra; Ceconi, Irene; Mendez, Daniel Gustavo; Buffarini, Miguel Angel; Sancho, Ana Maria; Gonzalez, Claudia Beatriz (2017)
The aim of this research was to study the effect of different handling conditions on physiological stress indicators and meat quality of beef cattle by studying animals with different temperaments. Forty animals classified by their temperament (calm and disturbed) were used. They were fed on pastures and finished with a mixed diet of corn grain and pasture. Biochemical indicators of animal stress were measured at slaughter (packed cell volume -PCV-, proteins, glucose, creatinine, alkaline phosphatase -APactivity, cortisol, insulin, glycogen). Also, ultimate pH and instrumental colour were chosen as meat quality markers. Animal temperament showed a significantly increase (p<0.05) on PCV levels and a significantly (p<0.05) decrease on muscle glycogen. Besides, levels of plasma glucose and total proteins showed significant (p<0.05) differences associated to management applied. Meat quality markers (pH and colour) did not show significant differences according to handling conditions or temperament. Mean cortisol levels at the exsanguination time were significantly higher (p<0.05) than the values obtained one week prior to slaughter, which suggests an important effect of stress associated to slaughter procedures. It would be interesting to focus attention on theassessment of acute stress at abattoir, in order to improve handling protocols, and therefore to assure meat quality in Argentinean beef production systems.